2007
DOI: 10.1158/1535-7163.mct-05-0285
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-κB p65 small interfering RNA or proteasome inhibitor bortezomib sensitizes head and neck squamous cell carcinomas to classic histone deacetylase inhibitors and novel histone deacetylase inhibitor PXD101

Abstract: Histone deacetylase inhibitors (HDI) can inhibit proliferation and enhance apoptosis in a wide range of malignancies. However, HDIs show relatively modest activity in head and neck squamous cell carcinomas (HNSCC), in which we have shown the activation of nuclear factor-KB (NF-KB; NF-KB1/RelA or p50/p65), a transcription factor that promotes expression of proliferative and antiapoptotic genes. In this study, we examined if HDIs enhance activation of NF-KB and target genes and if genetic or pharmacologic inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 58 publications
8
69
0
Order By: Relevance
“…Bortezomib enhances cell death caused by the death ligand tumor necrosis factor -related apoptosis-inducing ligand (21 -23), the BH3 mimetic GX15-070 (20), and the histone deacetylase inhibitors trichostatin A, sodium butyrate, and PXD101 (41). In addition, bortezomib has been shown to enhance the activities of the epidermal growth factor receptor inhibitors PKI166 and PD153035 (33,42).…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib enhances cell death caused by the death ligand tumor necrosis factor -related apoptosis-inducing ligand (21 -23), the BH3 mimetic GX15-070 (20), and the histone deacetylase inhibitors trichostatin A, sodium butyrate, and PXD101 (41). In addition, bortezomib has been shown to enhance the activities of the epidermal growth factor receptor inhibitors PKI166 and PD153035 (33,42).…”
Section: Discussionmentioning
confidence: 99%
“…However, Duan et al 18 reported that TSA promoted the acetylation of p65 and increased the NF-kB activity in head and neck cancer cells, which was responsible for the modest antitumor effect of TSA on these cancer cells. In this study, TSA enhanced the acetylation of p65 and accumulation of p65 in the nucleus of oral SCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…HDACi has been shown to inhibit deacetylation and increases the level of nuclear p65. 18 SAS cells were cultured in the presence or absence of 0.3 mM TSA, and the acetylated p65 was detected in combination with anti-p65 and anti-acetylated polypeptide antibodies. Acetylated p65 increased in a time-dependent manner from 6 h after the treatment (Figure 2a).…”
Section: Nuclear Accumulation Of Nf-kb By Infection With Hsv-1 Mutantmentioning
confidence: 99%
See 2 more Smart Citations